1989
DOI: 10.1002/jez.1402520111
|View full text |Cite
|
Sign up to set email alerts
|

De novo synthesis and release of polypeptides from cyclic and early pregnant porcine oviductal tissue in explant culture

Abstract: The objective of the present study was to identify and characterize in a limited manner the major de novo oviductal secretory proteins (OSP) synthesized and released by the porcine oviduct. Oviductal tissue was collected on various days of the estrous cycle (EC) and early pregnancy (EP) and cultured in a modified minimal essential medium supplemented with 100 muCi L-[3H]-leucine. Oviductal secretory activity, as measured by the rate of incorporation of 3H-leucine (dpm/mg wet tissue weight) into nondialyzable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 32 publications
3
55
0
3
Order By: Relevance
“…In sows, Iritani et al (1974) described no changes in protein concentration during the estrous cycle. A higher secretion rate of proteins has been described at proestrus and estrus when events such as fertilization and early cleavage stages of embryos occur (Buhi et al 1989). This would be more in agreement with our results showing a higher total amount of protein at estrus.…”
Section: Discussionsupporting
confidence: 93%
“…In sows, Iritani et al (1974) described no changes in protein concentration during the estrous cycle. A higher secretion rate of proteins has been described at proestrus and estrus when events such as fertilization and early cleavage stages of embryos occur (Buhi et al 1989). This would be more in agreement with our results showing a higher total amount of protein at estrus.…”
Section: Discussionsupporting
confidence: 93%
“…The strong correlations between these different characteristics support the concept that the oviduct environment is indeed associated with changes in steroids in the peri-ovulatory period. In particular, the inverse relationship between protein concentrations and the concentrations of P 4 is consistent with the findings of Buhi et al [8] who showed that porcine oviductal tissue during estrus has the highest levels of de novo protein synthesis and secretion. The temporal changes in pOSP mRNA expression and the secreted pOSP proteins in relation to the time of ovulation are consistent with evidence that pOSP expression is E 2 -dependent [11].…”
Section: Oviduct Flushingssupporting
confidence: 90%
“…Furthermore, de novo protein synthesis and secretion by explanted porcine oviducts was the highest for tissue recovered at estrus and was associated with elevated E 2 concentrations [8]. Finally, in Experiment 1, the highest total protein concentration was seen in oviduct flushings in the pre-ovulatory period and was associated with a higher E:P ratio.…”
Section: Oviduct Flushingsmentioning
confidence: 78%
“…Oviductal biosynthetic activity is greater under estrogen than progesterone domination. Significantly greater activity has been demonstrated in the oviduct of the pig [Buhi et al, 1989], sheep [Buhi et al, 1991] and cow [Geisert et al, 1987;Malayer et al, 1988] at estrus and at mid cycle in the human [Buhi, unpublished] than on other days of the cycle. Furthermore, this increase in biosynthetic activity is reflected in the activity of certain functional segments during the estrous cycle and early pregnancy ( fig.…”
Section: Biosynthetic Activitymentioning
confidence: 99%
“…1). In the pig [Buhi et al, 1989[Buhi et al, , 1997a, significantly increased synthesis and secretion was shown by the infundibulum and ampulla at estrus compared to other days of the cycle or early pregnancy. No change in activity was demonstrated for the isthmus regardless of day or status.…”
Section: Biosynthetic Activitymentioning
confidence: 99%